Toxicological Emergencies. Issue 1 (January 2023) - Azharuddin, Syed; Ogbebor, Osakpolor; Shuster, Mareena; Smith, Bridget; Arshad, Hammad; Cheema, Tariq
Abstract : Poisoning, drug overdose, and adverse drug effects continue to be a common encounter, especially in the intensive care unit (ICU). Patients are often critically ill or have a potential to rapidly deteriorate and warrant ICU admission. Adults suffering from overdoses rarely give a complete and accurate description of the quantity or type of medications ingested. In most adult cases, multiple substances are involved. A tentative diagnosis in most overdose and poisoning cases can be made by physical examination and simple laboratory tests (electrolyte panel, creatinine, serum osmolarity, urinalysis, etc). Supportive care, with particular attention to airway management, oxygenation, and circulation, is the mainstay of treatment. Basic treatment principles include limiting the amount of toxin absorbed, enhancing the elimination of ingested toxin, and preventing the conversion of non-toxic compounds to toxic metabolites. Drugs or poisons, where specific antidotes or effective therapies exist (especially acetaminophen, salicylates, methanol, ethylene glycol, and digitalis), should be aggressively sought and treated after initial stabilization has been accomplished. For those drugs or poisons where specific quantitative tests are available, levels should be obtained before treatment and may be repeated as clinically indicated.